2021
DOI: 10.3390/ijerph18105126
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Catastrophic Occupational Incidents among Electrical Contractors, 2007–2013

Abstract: This study used methodologies of descriptive and quantitative statistics to identify the contributing factors most affecting occupational accident outcomes among electrical contracting enterprises, given an accident occurred. Accident reports were collected from the Occupational Safety and Health Administration’s fatality and catastrophe database. To ensure the reliability of the data, the team manually codified more than 600 incidents through a comprehensive content analysis using injury-classification standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…A previous study of 621 catastrophic occupational incidents among electrical contractors from 2003 to 2017 found six factors having significant effects on the fatality rates of electrical contractors in the construction industry, with nature of injury and part of body injured having the strongest association, while project type, source of injury, event type, and fatality cause exhibiting moderate association. 33 Our study revealed accident factors such as gender, age, accident date, location, union status, part of body, human factor, event type, project type, project cost, construction operation cause, fatality cause, electrical event, and source of injury exhibited significant effects on fatalities and serious injuries in electrical occupations.…”
Section: Contributory Factorsmentioning
confidence: 78%
See 1 more Smart Citation
“…A previous study of 621 catastrophic occupational incidents among electrical contractors from 2003 to 2017 found six factors having significant effects on the fatality rates of electrical contractors in the construction industry, with nature of injury and part of body injured having the strongest association, while project type, source of injury, event type, and fatality cause exhibiting moderate association. 33 Our study revealed accident factors such as gender, age, accident date, location, union status, part of body, human factor, event type, project type, project cost, construction operation cause, fatality cause, electrical event, and source of injury exhibited significant effects on fatalities and serious injuries in electrical occupations.…”
Section: Contributory Factorsmentioning
confidence: 78%
“…A previous study of 621 catastrophic occupational incidents among electrical contractors from 2003 to 2017 found six factors having significant effects on the fatality rates of electrical contractors in the construction industry, with nature of injury and part of body injured having the strongest association, while project type, source of injury, event type, and fatality cause exhibiting moderate association 33 …”
Section: Discussionmentioning
confidence: 96%
“…The 17 cost items consisted of the following: (1) income loss cost, (2) tax, (3) health insurance, (4) national insurance, (5) employment insurance, (6) human cost, (7) medical care benefits, (8) temporary disability compensation benefits, (9) survivor's benefits, (10) funeral service expense, (11) workers' compensation insurance, (12) settlement cost, (13) others, (14) penalty, (15) fine, (16) delay reimbursement cost, and (17) administrative loss cost.…”
Section: Results Of Proposed Framework Developmentmentioning
confidence: 99%
“…According to Sunindijo and Zou [11], fatalities in the construction industry account for about 30-40% among all industries. This stems from the characteristics of what is considered a dangerous industry; specifically, the construction industry has relatively low safety performance when considering injury rates [12][13][14]. Lee et al [15] reported that the number of fatalities continues to increase, with construction sites now considered among the most dangerous workplaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation